2004
DOI: 10.1128/jb.186.7.1945-1958.2004
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic Comparison of Manganese- and Iron-Dependent Homoprotocatechuate 2,3-Dioxygenases

Abstract: The X-ray crystal structures of homoprotocatechuate 2,3-dioxygenases isolated from Arthrobacter globiformis and Brevibacterium fuscum have been determined to high resolution. These enzymes exhibit 83% sequence identity, yet their activities depend on different transition metals, Mn 2؉ and Fe 2؉ , respectively. The structures allow the origins of metal ion selectivity and aspects of the molecular mechanism to be examined in detail. The homotetrameric enzymes belong to the type I family of extradiol dioxygenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
173
1
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(187 citation statements)
references
References 84 publications
8
173
1
5
Order By: Relevance
“…This reaction presumably is catalyzed by an iron(II)-dependent extradiol dioxygenase (93). These enzymes generally contain a His 2 -carboxylate triad involved in binding the iron atom (49,75,78,79,82,89). A BLASTP search for HapD sequence homologs in the microbial genome database revealed a small number of proteins (in Pseudomonas aeruginosa PA7, Photorhabdus luminescens subsp.…”
Section: Discussionmentioning
confidence: 99%
“…This reaction presumably is catalyzed by an iron(II)-dependent extradiol dioxygenase (93). These enzymes generally contain a His 2 -carboxylate triad involved in binding the iron atom (49,75,78,79,82,89). A BLASTP search for HapD sequence homologs in the microbial genome database revealed a small number of proteins (in Pseudomonas aeruginosa PA7, Photorhabdus luminescens subsp.…”
Section: Discussionmentioning
confidence: 99%
“…1, II) (4,8) The X-ray crystal structures of several extradiol dioxygenases have shown that, as predicted, the substrate does chelate the iron and this creates a vacant site in the iron coordination (5,9,10). The structures have also allowed the application of computationally-based theoretical techniques, leading to several new proposals for the mechanism of the O-O bond cleavage and ring opening step(s) (11,12).…”
mentioning
confidence: 91%
“…2,4,[6][7][8][9] This directly displaces two solvents from the "catalytic" face of the facial triad. The third solvent bond to the iron (if present) is weakened or broken by the donation of charge from the anionic catecholic ligand.…”
Section: Introductionmentioning
confidence: 99%